2015
DOI: 10.1371/journal.pone.0128886
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a and MiR-374a Function as Novel Regulators of Cisplatin Resistance in Human Ovarian Cancer A2780 Cells

Abstract: Chemoresistance remains a major obstacle to effective treatment in patients with ovarian cancer, and recently increasing evidences suggest that miRNAs are involved in drug-resistance. In this study, we investigated the role of miRNAs in regulating cisplatin resistance in ovarian cancer cell line and analyzed their possible mechanisms. We profiled miRNAs differentially expressed in cisplatin-resistant human ovarian cancer cell line A2780/DDP compared with parental A2780 cells using microarray. Four abnormally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 30 publications
(31 reference statements)
2
62
0
Order By: Relevance
“…Certain miRs may improve chemotherapy sensitivity, whereas others may induce chemoresistance of cancer cells (24)(25)(26). In ovarian cancer, miR-130a and miR-374a were demonstrated to function as negative regulators of cisplatin resistance in A2780 cells (27), whereas miR-31 positively regulated cisplatin resistance in numerous ovarian cancer cells (28). In the present study, miR-20a was identified as a novel positive regulator for OVCAR3 cells cisplatin resistance and migration.…”
Section: Discussionsupporting
confidence: 47%
“…Certain miRs may improve chemotherapy sensitivity, whereas others may induce chemoresistance of cancer cells (24)(25)(26). In ovarian cancer, miR-130a and miR-374a were demonstrated to function as negative regulators of cisplatin resistance in A2780 cells (27), whereas miR-31 positively regulated cisplatin resistance in numerous ovarian cancer cells (28). In the present study, miR-20a was identified as a novel positive regulator for OVCAR3 cells cisplatin resistance and migration.…”
Section: Discussionsupporting
confidence: 47%
“…Bladder cancer (BC), one of the most prevalent carcinomas worldwide, has been identified as the fourth and tenth leading cause of cancer-related deaths in males and females, respectively (1). Despite many efforts have been made, the prognosis still remains unsatisfied.…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that multiple miRNAs participate in ovarian cancer drug-resistance, including miRNA-130a and miRNA-374a (14). miRNA-152 and miRNA-185 were demonstrated to be significantly downregulated in SKOV3/DDP and A2780/DDP cells (14). Previous studies have demonstrated that miRNA-21 is involved in drug resistance in multiple types of cancer, including gastric, breast and lung cancer, via regulation of PTEN (7,8,15).…”
Section: Discussionmentioning
confidence: 50%
“…Although platinum-based chemotherapy has improved the prognosis of ovarian cancer, drug-resistance remains the main obstacle to successful treatment. The present study revealed that multiple miRNAs participate in ovarian cancer drug-resistance, including miRNA-130a and miRNA-374a (14). miRNA-152 and miRNA-185 were demonstrated to be significantly downregulated in SKOV3/DDP and A2780/DDP cells (14).…”
Section: Discussionmentioning
confidence: 58%